Final examination question generator using microsoft word's macro - Hoong, Adrian Yong Weng (2014)
The Final Examination Question Paper Generator is developed to assists lecturers of Faculty of Computer System & Software Engineering, Universiti Malaysia Pahang to be more efficient in producing a high quality final examination question paper, able to identify the Bloom's Taxonomy cognitive level of questions and producing a question paper that complies with Universiti Malaysia Pahang's final examination question paper format. This project is to develop a functional Final Examination Question Paper that complies with Universiti Maaysia Pahang's final examination question paper specifications. The system developed is an add-in to Microsoft Word 2010 which is developed using Rapid Application Development model. By using this model fast prototypes and various tests can be made. This system is developed using Visual Basic for Application which is sub-language of Visual Basic but is tailored to further extend the functionalities of Microsoft's application. In conclusion, this project is a Final Examination Question Paper Generator which is able to produce high quality final examination question paper in terms of formatting and questions.